Study of the MUI DSN Fatwa on Clause Fines and Compensation on the Sharia KPR - Hasanuddin Ingka; Fakhruddin Mansyur; Mega Mustika (LAA MAISYIR: Jurnal Ekonomi Islam, 2020)
This research was conducted to examine the DSN MUI fatwa related to sanctions on fines and compensation for customers due to delaying payments, the sanctions given to capable customers who delay payments and to find out the application of the DSN-MUI Fatwa. This research was a qualitative research with primary data sources from interviews with the marketing coordinator and the service coordinator and documentation. The analysis in this discussion was descriptive qualitative data analysis. The results of this study indicate that the application of sanctions for fines and compensation for customers by banks based on the MUI DSN fatwa there were still some scholars who do not agree with this because the fatwa does not include specific criteria, thus the analysis of all Islamic banks taking mortgages in Islamic banking are capable people, but on the way there are those who are constrained by payment, such as traders whose income is uncertain. In this study it was also found that this was enforced by Islamic banking due to disciplining customers and company losses.